2012
DOI: 10.1111/j.1574-6968.2012.02567.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of catalase to hydrogen peroxide resistance in Enterococcus faecalis

Abstract: Enterococcus faecalis exhibits high resistance to oxidative stress. Several enzymes are responsible for this trait. The role of alkyl hydroperoxide reductase (Ahp), thiol peroxidase (Tpx), and NADH peroxidase (Npr) in oxidative stress defense was recently characterized. Enterococcus faecalis, in contrast to many other streptococci, contains a catalase (KatA), but this enzyme can only be formed when the bacterium is supplied with heme. We have used this heme dependency of catalase activity and mutants deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 17 publications
1
25
2
Order By: Relevance
“…This may be due to the presence of detoxifying enzymes such as peroxidases and catalases (Baureder et al . ). In addition, previous studies reported that PAA action is both time‐ and concentration‐dependent, so that longer exposure times and higher concentrations could show higher antimicrobial activity, similar that of to NaOCl (Guerreiro‐Tanomaru et al .…”
Section: Discussionmentioning
confidence: 97%
“…This may be due to the presence of detoxifying enzymes such as peroxidases and catalases (Baureder et al . ). In addition, previous studies reported that PAA action is both time‐ and concentration‐dependent, so that longer exposure times and higher concentrations could show higher antimicrobial activity, similar that of to NaOCl (Guerreiro‐Tanomaru et al .…”
Section: Discussionmentioning
confidence: 97%
“…Among many other components, blood contains serum, hemin and hemoglobin24 but the hemolytic capacity of pathobionts can also increase their concentration25. It is already described that hemoglobin and hemin have a peroxidase activity172627. P. intermedia and P. gingivalis also generate layers of haems with catalytic activity to degrade the H 2 O 2 using hemin and hemoglobin28.…”
Section: Discussionmentioning
confidence: 99%
“…However, this appears a priori in contradiction with the higher susceptiblity of the null-mutant strain to both in vitro oxidative stress and oxidative burst in mouse macrophages. Despite the fact that enterococci possess a kat gene, catalase enzyme can only be formed when heme or manganese is present and these organisms are considered as catalase-negative bacteria [48], [49]. While little is known about mechanisms of oxidative stress response in E. faecium , it has been shown in E. faecalis that peroxidases important for the survival under oxidative stress and into macrophages are Tpx (thiol peroxidase), Npr (NADH peroxidase), and Ahp (alkyl hydroperoxide reductase) [50], so that E. faecium homologs are not upregulated in the Δ asrR mutant.…”
Section: Discussionmentioning
confidence: 99%